The Relationship Between Internet Pornography and Adolescent Cyberbullying Behavior - Hashinawati, Hanadhia Irbah; Sutrisna, I Putu Belly (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2023)
The internet plays a pivotal role in facilitating human communication, education, and entertainment. Internet users reach 4,7 million out of a total world population of 7,8 million. Nonetheless, the influence of internet is twofold, as it engenders adverse consequences for adolescents. Cyberbullying and internet pornography, in particular, have been indentified as significant contributor to the deterioration of mental health. A cross-sectional analytic descriptive study had done. There was a ninety-two respondent who fulfilled the online questioner from January 20th to 27th 2023. SPSS version 26, chi-square test and multiple logistic regression test done to do statistical analysis. Around 47.8% respondent accessed internet pornography and 22.8% had done cyberbullying. There was a relationship between internet pornography with adolescent cyberbullying behavior (p <0.05). Internet pornography risked around four times higher than adolescent cyberbullying behavior. Internet can easily connect to pornography by 3A: accessibility, affordability and anonymity. Wrigth and Donnerstein (2014) stated nearly 42% of adolescent watched pornography on internet, which around 27% watched it accidentally. Pornography can change someones mind or behavior. Shek and Ma (2014) concluded that cyberbullying person were more likely to access internet pornography. Adolescent is an aged of growth and taking risk. They do not fully understand about their actions and consequences of what they have done